Pengolahan Sampah Berbasis Limbah Pantai di Pulau Lemukutan - Muliadi Muliadi; Shifa Helena; Arie K Kushadiwijayanto; Yusuf Nurrahman; Sy. Irwan Nurdiansyah; Dwi Imam Prayitno (Berdikari: Jurnal Inovasi dan Penerapan Ipteks, 2022)
The high number of tourists who come to Lemukutan Island has a significant impact on the volume of waste. This activity aims to instill and increase the knowledge of tourism managers and visitors in waste management. The method used is socialization through the coastal activity of the Lemukutan Island community with students by picking up trash. Furthermore, the waste is separated into organic, plastic, metal, and glass waste. The results of the action of picking up garbage around Lemukutan Island obtained 90 kg of organic waste, 45 kg of plastic groups, and 77 kg of garbage, plastic/mica drink bottles, cans, and glass. The organic waste obtained is then buried in the ground to become compost. The results of this program show public awareness of a clean and healthy environment, especially in the tourist destination of Lemukutan Island. The success of this program is supported by the togetherness of the community and universities in determining strategic steps to protect the environment of Lemukutan Island.